Criminal Law and Freedom of Opinion in the Era of Digital Democracy (Case Study in Indonesia) - Dave Advitama; Basuki Rekso Wibowo; Rio Christiawan; Gunawan Widjaja (Green Publisher Indonesia, 2025)
Freedom of opinion in Indonesia, constitutionally guaranteed as a human right, faces challenges in the digital era due to the ambiguous enforcement of the ITE Law, which initially targeted cybercrimes but expanded to regulate online speech, risking democratic expression. This study analyzes the ITE Law’s evolution (2008–2024) to assess its impact on freedom of expression in digital democracy, focusing on legal shifts and enforcement practices. Using normative juridical research, the study examines secondary legal materials through qualitative analysis, including legislation, court decisions, and scholarly works. The 2024 revisions reduce penalties and limit complaints to directly affected individuals, aiming to curb repression. However, ambiguities persist in defamation provisions, and enforcement biases threaten free speech. The study underscores the need for clearer legal standards, digital literacy programs, and alternative dispute mechanisms to align the ITE Law with democratic principles. Future research should explore comparative models and the law’s societal impact post-revision.